Economic development and environmental sustainability policies and principles for a durable equilibrium - Furtada, Jose I dos R (Ed.)_; World Bank; Belt, Tamara (Ed.); Jammi, Ramachandra (Ed.) (Washington World Bank, 2000)
The book concludes by looking of planning and envirnmental indicators and underlining the importance of information and knowledge.This implies that for more economics development will be required to achieve acceptable minimal standards of living for every
This book is based on seminars conducted by the World Bank in collaboration with the Foundation for Advanced studies on international development, Japan
Keywords: Sustainable development-Congresses; Economic development-Environmental aspects-Congresses; Environmental policy